Munsell Notation System and CIELab as a tool for evaluation colors in soils - Domínguez Soto, Julia María; Román Gutiérrez, Alma Delia; Prieto García, Francisco; Acevedo Sandoval, Otilio (Revista Mexicana de Ciencias Agrícolas, 2018)
The color is one of the most important morphological features, the most obvious, easy to determine and relevant taxonomic identification of soils. The color of soils is closely related with the solid components (organic matter, texture, mineralogical composition, morphology) being the transition metals, mainly those soils can provide this characteristic. Munsell Notation System and CIELab are two techniques for determining the color of the soil. The aim of this study is to evaluate the physical, chemical and mineralogical properties of Denganthza hill ́s soil, and its relationship with the characteristic color showed in the samples, using methods of assessment color Munsell Notation System and CIELab Spectrophotometric System. In the Munsell Notation System soils have colors from pale yellow to reddish to values between 2.5Y, 5Y, 2.5YR, 7.5YR and 10YR showing clear staining indicating a depletion of Fe and Mn, leading to suggest that due to palaeosols causes, there has been a podzolization process. In CIELab color of the soils studied are located in quadrants +a* and +b∗ and correspond to red and yellow, the color of wet soils corresponds to a reddish-yellow, high a higher yellow saturation occurring in the soils 1, 6 and 13, the rest is a trend toward lighter shades, but in dry soils shows the same yellow-red, without saturation with light shades in all samples.
Keywords: color; spectrophotometry; systems; soil